CHALLENGES AND FUTURE DIRECTIONS OF BIOACTIVE SCAFFOLDS IN CRANIOFACIAL RECONSTRUCTION (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Craniofacial reconstruction presents substantial regenerative challenges owing to the intricate interactions between osteogenesis, angiogenesis, and immune modulation within a highly specialized anatomical framework. Bioactive scaffolds have emerged as essential tools for addressing these challenges by offering osteoconductive matrices that support cellular infiltration and vascular integration. Recent advancements in B-TCP/PLLA composite scaffolds have shown improved biodegradation kinetics and mechanical stability; however, translational barriers remain, including insufficient neovascularization, inflammatory dysregulation, and biomechanical mismatches. This review synthesizes current scaffold technologies, focusing on mechanistic insights into scaffold-host interactions and the regenerative microenvironment. Key limitations, such as the timing of scaffold degradation cascades, immune polarization, and vascular insufficiency, are critically evaluated. The review further outlines future directions involving smart biomaterials with stimuli-responsive properties, AI-assisted scaffold optimization, and personalized regenerative medicine approaches that incorporate 3D/4D bioprinting technologies. These innovations have the potential to overcome existing translational bottlenecks by enabling adaptive, patient-specific regenerative systems. This narrative review aims to provide a comprehensive, mechanistically informed framework to guide the next generation of bioactive scaffold design and clinical implementation in craniofacial reconstruction.
Keywords: insufficient neovascularization, inflammatory dysregulation, and biomechanical mismatches